Società Italiana di Medicina del LavoroPosition Paper Amianto - Apostoli, Pietro (Med Lav, 2019)
«Position Paper on Asbestos of the Italian Society of Occupational Medicine». The Position Paper (PP) on asbestos of the Italian Society of Occupational Medicine (SIML) aims at providing a tool to the occupational physician to address current diagnostic criteria and results of epidemiological studies, and their consequences in terms of preventive and evaluation actions for insurance, compensation and litigation. The PP was based on an extensive review of the scientific literature and was compiled by a Working Group comprising researchers who have contributed to the international literature on asbestos-related diseases, as well as occupational physicians with extensive experience in the evaluation of risks and the medical surveillance of workers currently and formerly exposed to asbestos. The PP was drafted and reviewed between 2017 and 2018; its final version was prepared according to the guidelines of AGREE Reporting Checklist. All the members of the Working Group subscribed to the document, which was eventually approved by SIML’s Executive Committee. The first section addresses industrial hygiene issues, such as methods for environmental monitoring, advantages and limitations of different microscopy techniques, the potential role of microfibers and approaches for retrospective assessment of exposure, in particular in epidemiological studies. The second section reviews the biological effects of asbestos with particular attention to the diagnostic aspects of asbestosis, pleural changes, mesothelioma and lung cancer. In the following section the criteria of causal attribution are discussed, together with different hypotheses on the form of the risk functions, with a comparison of the opinions prevalent in the literature. In particular, the models of the risk function for mesothelioma were examined, in the light of the hypothesis of an acceleration or anticipation of the events in relation to the dose. The last section discusses topics of immediate relevance for the occupational physician, such as health surveillance of former exposed and of workers currently exposed in remediation activities.